The Multifaceted Roles of MSCs in the Tumor Microenvironment: Interactions With Immune Cells and Exploitation for Therapy - Papait, Andrea; Stefani, Francesca Romana; Cargnoni, Anna; Magatti, Marta; Parolini, Ornella; Silini, Antonietta Rosa (Frontiers in Cell and Developmental Biology, 2020)
The tumor microenvironment (TME) plays a critical role in tumorigenesis and is comprised of different cellular components, including immune cells and mesenchymal stromal cells (MSC). In this review we will discuss MSC in the TME setting and more specifically their interactions with immune cells and how they can both inhibit (immunosurveillance) and favor (immunoediting) tumor growth. We will also discuss how MSC are used as as a therapeutic strategy in cancer. Due to their unique immunomodulatory properties, MSC isolated from perinatal tissues are intensely explored as therapeutic interventions in various inflammatory-based disorders with promising results. However, their therapeutic applications in cancer remain for the most part controversial and, importantly, the interactions between administered perinatal MSC and immune cells in the TME remain to be cleary defined.